Zur Beziehung der Theologie zu den übrigen Wissenschaften, speziell der praktischen Theologie zu den Humanwissenschaften - Mette, Norbert (European Journal of Mental Health, 2011)
Some Remarks on the Relationship between Theology and Other Disciplines with Special Attention to Practical Theology vis-à-vis the Humanities: When we examine the history of the relationship between (Catholic) theology and other academic disciplines, in an ideal and typical case, it is possible to distinguish several characteristic phases. At the beginning theology rejected new disciplines such as psychology, sociology, etc. but later it began to show interest in their methodology and started to apply their methods itself. Theology utilized the humanities for its own purposes as auxiliary disciplines or tools until, as a next step, these disciplines gained independence (pastoral psychology, pastoral sociology) and became integrated into theology as equal partners. At present, the humanities are considered equal partners that have to be cooperated with. The question is in what ways theology itself can contribute to this interdisciplinary dialogue.